Solid Waste Management for Environmental Sustainability and Human Health - Dr. Sophia Ansari, Dr. Tarun Madan Kanade, Dr. Jonathan Joseph; Dr. Tushar Savale, Mrs. Ashima Manoj Varghese (Journal of Informatics Education and Research, 2024)
The paper titled "Solid Waste Management for Environmental Sustainability and Human Health" provides a comprehensive exploration of strategies for the industry to embrace environmentally sustainable practices while safeguarding human health. The foundation is laid through a meticulous assessment of the industry's waste landscape, followed by the establishment of principles grounded in the 3R approach, circular economy integration, and life cycle thinking. The model emphasizes the adoption of advanced technologies, such as efficient recycling and innovative waste-to-energy solutions, along with compliance with stringent policies and regulations. Recognizing the pivotal role of community engagement, the model encourages industry collaboration with local communities, proactive education initiatives, and transparent reporting. Monitoring and evaluation mechanisms, including key performance indicators and regular audits, ensure the effectiveness of waste management initiatives. Moreover, the model underscores the importance of innovation and future-readiness, calling for industry investment in research and development to address emerging challenges. Corporate social responsibility is seamlessly integrated, extending sustainable practices to the supply chain and fostering community investments. The model embraces a philosophy of continuous improvement and adaptation, urging industry players to solicit feedback, learn from mistakes, and remain agile in the face of evolving environmental and social landscapes. By incorporating these elements, the model provides a holistic framework for industry-wide adoption, fostering a paradigm shift towards sustainable solid waste management practices that prioritize both environmental well-being and human health.